The Role of Subjective Well-Being (SWB) and Trust in the Employer on Organizational Citizenship Behavior (OCB) of Industrial Employees in the Industrial Revolution Era - Teguh Iman Santoso; Kuswoyo Kuswoyo; Moch Aminudin Hadi; Syaifullah Syaifullah; Ratna Komala Putri (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
The purpose of this study was to analyze the role of Subjective Well-Being and Trust in the Employer on Organizational Citizenship Behavior (OCB) of Industrial Employees in the industrial revolution era. This research method is quantitative through surveys, data obtained by distributing online questionnaires which are distributed via social media. Respondents in this study were 300 permanent manufacturing employees with a minimum working period of three years, status as permanent employees. The selection of research subjects was carried out nonprobability by using purposive sampling technique because it is based on predetermined characteristics. This study uses a Likert model scale of 1 to 7 as the main instrument in obtaining empirical data from organizational citizenship behavior, subjective well-being, and trust in the employer. Data analysis used structural equation modeling (SEM) with data processing tools using SmartPLS 3.0. The stages of data analysis were validity, reliability, termination coefficient and hypothesis testing. The results of this study are that subjective Well-Being has a positive and significant effect on Organizational Citizenship Behavior (OCB), Trust in The Employer has a positive and significant effect on Organizational Citizenship Behavior (OCB) and Subjective Well-Being has a positive and significant effect on Trust. in The Employer.